Excitation of isomer in 115In(γ,γ′) 115mIn reaction - Shevchenko, O.S.; Dovbnja, A.N.; Kuplennikov, E.L.; Nemashkalo, A.A.; Noga, V.I.; Ranyuk, Y.N. (Вопросы атомной науки и техники, 2005)
Activation yield measurements of the 115In(γ,γ′) 115mIn reaction were performed with bremsstrahlung of endpoint energies in the range of Eϒ max ≤ 0.8…3.0 MeV. The integrated cross sections for some intermediate states (IS) were deduced from the measured yield curve. It is shown, that increased of the reaction yield at the energy range of 1.6 … 3.0 MeV can be connected with existence of strong intermediate levels at the energy of 1999 and 2420 keV. Вимірювання активаційного виходу 115In(γ,γ′) 115m In реакції проведені на гальмовому випромінюванні в області граничних енергій Eϒ max ≤ 0.8…3.0 МеВ. Інтегральні перерізи для кількох проміжних станів отримані з аналізу кривої вихода. Доведено, що зростання виходу в інтервалі 1.6…3.0 MеВ може бути пов’язано з існуванням сильних проміжних рівнів з енергією 1999 та 2420 кеВ. Измерения активационного выхода 115In(γ,γ′) 115m In реакции проведены на тормозном пучке в области граничных энергий Eϒ max ≤ 0.8…3.0 МэВ. Интегральные сечения для ряда промежуточных состояний получены из анализа кривой выхода. Показано, что рост выхода реакции в интервале 1.6…3.0 MэВ может быть связан с существованием сильных промежуточных уровней с энергией 1999 и 2420 кэВ.